An ultrastructural study of testes permeability in sea urchins, Strongylocentrotus intermedius. (January 2015) - Kalachev, Alexander V.
Highlights: Testes permeability in a sea urchin was studied with transmission electron microscopy. The germinative epithelium in the testis is subdivided into two compartments. An incomplete permeability barrier was found in the testes. Abstract: Permeability of testes in sea urchins, Strongylocentrotus intermedius, was investigated by using an electron-opaque tracer, lanthanum nitrate. This tracer is able to enter the basal compartment of germinative epithelium, where developing germ cells are located. However, its ability to penetrate the gonadal lumen was reduced. An incomplete permeability barrier between the basal compartment and the gonadal lumen is supposed to exist in testes of S . intermedius .